O falso documentário como enunciador de ruídos no regime de verdade - Borges, Leandro Martins (2014)
This research investigates in which way the documentary, understood here as a regime of truth, is contested by the documentary production known as fake documentary. This genre appropriates the esthetic/narrative documentary forms in order to tell a fictional story. We consider that it is possible to criticize the very construction of the regimes of truth in a subversive way through its mimicry. This approach the subversive power within the fake documentary is not found in the few studies on the subject. Jane Roschoe s and Alexandra Juhasz s books, along with Matheus Barbosa Emérito s dissertation analyze the fake documentary from its formal aspects, seeing it as a parody or a deconstruction of the documentary. Our proposal is to build a film analysis of two fake documentaries chosen for their capability to generate a double critique of the regime of truth, present both in the cinematographic aspect and in the subject of the movies. From the theories of discourse and the concepts developed by Foucault, i ek and Lacan, relating regime of truth, falseness and ideology, we analyze the films Exit Through The Gift Shop and Opération Lune. As an expected result there is the possibility of perceiving how a film genre, typically associated with its commitment to the truth, can be paradoxically a means used subversively to generate noise in the regimes of truth. This paper intends to analyze the cinematographic resources that make a movie being classified as a documentary possible, and how the fake documentary uses the same resources to carry out a subversive critique of the regimes of truth related to the subject of each film